hnRNP A1B, a Splice Variant of HNRNPA1, Is Spatially and Temporally Regulated - Gagné, Myriam; Deshaies, Jade-Emmanuelle; Sidibé, Hadjara; Benchaar, Yousri; Arbour, Danielle; Dubinski, Alicia; Litt, Gurleen; Peyrard, Sarah; Robitaille, Richard; Sephton, Chantelle F.; Vande Velde, Christine (Frontiers in Neuroscience, 2021)
RNA binding proteins (RBPs) play a key role in cellular growth, homoeostasis and survival and are tightly regulated. A deep understanding of their spatiotemporal regulation is needed to understand their contribution to physiology and pathology. Here, we have characterized the spatiotemporal expression pattern of hnRNP A1 and its splice variant hnRNP A1B in mice. We have found that hnRNP A1B expression is more restricted to the CNS compared to hnRNP A1, and that it can form an SDS-resistant dimer in the CNS. Also, hnRNP A1B expression becomes progressively restricted to motor neurons in the ventral horn of the spinal cord, compared to hnRNP A1 which is more broadly expressed. We also demonstrate that hnRNP A1B is present in neuronal processes, while hnRNP A1 is absent. This finding supports a hypothesis that hnRNP A1B may have a cytosolic function in neurons that is not shared with hnRNP A1. Our results demonstrate that both isoforms are differentially expressed across tissues and have distinct localization profiles, suggesting that the two isoforms may have specific subcellular functions that can uniquely contribute to disease progression.